Development of interactive multimedia related information about senior high school on guidance and counseling - Badrujaman, Aip; Cahyawulan, Wening; Debasari, Lulu Arini (Universitas Negeri Padang, 2018)
This study aims to develop interactive multimedia as a viable medium to be used in individual planning services about information on State High Schools in the school zone for the domicile of the new Kebayoran sub-district. The research was conducted at Purnama Middle School in Jakarta. The research used is the ADDIE development model with three stages, (1) analysis, (2) design and (3) development. The instruments used were expert validation questionnaires and user trial questionnaires. The data analysis technique used is formative evaluation techniques. The results of material validation show the category â€œvery feasibleâ€ with a percentage of 83.33%. Then the results of media validation show the category â€œvery feasibleâ€ with a percentage of 91.11%. The results of user trial conducted on five students showed the category â€œfeasibleâ€ in the aspect of the media with a percentage of 81.6%, the category â€œfeasibleâ€ in the material aspect with a percentage of 79%, and the category â€œvery feasibleâ€ in the aspect media with a percentage of 82%.